Electronic journals : Their use and impact in the portuguese universities output - Costa, Teresa (2014)
The availability of electronic journals in the Portuguese academic community improved in a spectacular way since the creation of the national university consortium, Online Knowledge Library (b-on), in 2004. The work presented here is the outcome of a line of research begun in 2011 which aims to investigate the supply and use of electronic journals incorporated into university libraries through b-on. This study aims to present and analyse some of the statistical and bibliometric indicators of the Portuguese scientific consumption and output seeking to evaluate its connection with b-on. It was analysed the usage of b-on resources by the public universities members of the consortium, from 2004 to 2010.In addition to the usage data of the consortium, we used the Web of Science (WoS) from which we identified the articles indexed by five Portuguese universities between 2000-2010.